Educate Girls : Improving the Quality and Outcomes of Girls’ Learning - Agapitova, Natalia (World Bank, Washington, DC, 2017)
In India, women and girls, especially in rural areas, are particularly affected by illiteracy. The social enterprise educate girls works to reform the existing school framework and create community ownership of government schools to improve Indian girls’ enrollment, retention, and academic performance. As of fiscal year 2017-18, educate girls operates in 10 districts in Rajasthan and 3 districts in Madhya Pradesh benefiting approximately 3.8 million beneficiaries. Educate girls creates community ownership of government schools by leveraging existing public, private, and community resources to empower the local communities. The educate girls model allows for sending one girl to school at United States dollar (USD) 5 per year. Its monitoring and evaluation system measures enrollment, attendance, and quality of learning for these girls, even at a large scale. The program’s impact is assessed through rigorous evaluation techniques, including quasi-experimental designs and randomized control trials. The educate girls model has the potential for far-reaching benefits - continuing to address gender inequality in education can bring about real transformation, such as improvements in health, income levels, and overall livelihoods in rural populations.